PENGARUH STRATEGI POE TERHADAP HASIL BELAJAR MATERI PERPINDAHAN KALOR DI SMP - Megawati, Megawati; Maria S, Haratua Tiur; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to investigate the influence of Predict-Observe-Explain (POE) learning strategy to the learning outcomes of the students of class VII of heat transfer at Junior High School Kristen Maranatha Pontianak. The types of research used are quasi-experimental research design with nonequivalent control group design, the sample consisted of two classes of VII A as the experimental class and class VII C as the control class with a total sample of 67 students, which are chosen by the group intact. The tools of Data Collection used is in the form of a test of 7 questions. Based on t test obtained Asymp sig 0.000 <0.025  then Ha accepted means of learning outcomes of students who take poe learning strategies (experimental group) was higher than the students who take the conventional learning (control group). Thus it can be concluded that the learning strategy of POE can improve student learning outcomes by 43.62% with effect size 0.93 (high category). This POE learning strategy can be used as an alternative to physics learning in school.Keywords:  Learning Result, Predict-Observe-Explain (POE) Heat Transfer.